D&D dungeon club. 2, Time to party - Ostertag, Molly Knox (Ostertag, Molly Knox. D&D Dungeon Club, 2024)
"The party continues but the problems get bigger in this second installment of this original Dungeons & Dragons graphic novel series brought to you by New York Times bestselling author Molly Knox Ostertag and critically acclaimed illustrator Xanthe Bouma. Olivia loves being the Dungeon Master of her after-school club, creating a world with magic and epic battles with adventure around every corner. She's always felt at home in her game, but now--with new members and new plotlines--her world has gotten more complicated than ever. It doesn't help when Olivia's older sister, Lu, comes home from college and brushes off all Olivia's hard work, telling her to get real. A seed of doubt is planted, and suddenly the colorful world of her game starts to fade around her. Will Olivia be able to keep everything from changing, or will the party fall apart?"--Amazon.com.